One-bit maximum likelihood algorithm for sensor networks in non-ideal channels - Nana WANG; Zhaoting LIU; Yingbiao YAO (Dianxin kexue)
Wireless sensor networks typically consist of wireless sensor nodes that are distributed in a certain spatial range.In general,the energy storage,computing and communication capabilities of nodes are extremely limited.Direct transmission of the sampled signals of the various nodes to the fusion center will result in more energy consumption and greater network communication load.If the sampled signal value of each sensor node is compressed into a one-bit measurement value and then transmitted,the energy consumption and the communication load can be greatly reduced.The parameter estimation problem based on one-bit measurement of sensor networks in multiplicative noise environment was studied.Considering the non-ideal binary channel with interference between the node and the fusion center,a parameter estimation algorithm based on maximum likelihood was proposed,Cramér-Rao lower bound of the parameter estimation was analyzed,and the effectiveness of the algorithm was verified through a series of simulation experiments.